Trends in low‐density lipoprotein‐cholesterol blood values between 2012 and 2017 suggest sluggish adoption of the recent 2013 treatment guidelines. Issue 1 (30th November 2018) - Superko, H. Robert; Williams, Paul T.; Dansinger, Michael; Schaefer, Ernst
Abstract : Background: Over a 14‐year period, age‐adjusted high total cholesterol (≥240 mg/dL) in the United States declined from 18.3% in 1999 to 2000 to 11.0% in 2013 to 2014, coinciding with the 2001 National Cholesterol Education Program Adult Treatment Panel (ATP)‐III guidelines that endorsed low‐density lipoprotein (LDL)‐cholesterol blood value goals. Statin treatment recommendations were revised by the American College of Cardiology and the American Heart Association (ACC/AHA) in November 2013 to a "risk‐based prescription" approach that did not utilize blood cholesterol values. This increased dosage and expanded the statin‐eligible population by an estimated 12.8 million US adults. These changes should further lower total and LDL cholesterol concentrations nationally. Methods: We examined data from 507 752 patients nationally aged ≥16 years whose fasting bloods were sent to Boston Heart Diagnostics for direct LDL‐cholesterol measurements. Between 2012 and 2017, age‐adjusted concentrations were examined by analysis of covariance and LDL‐cholesterol ≥160 mg/dL by logistic regression. Results: Contrary to expectations, age‐adjusted mean LDL‐cholesterol concentrations (±SE, mg/dL) increased significantly ( P < 10 −16 ) in men (2012:113.8 ± 0.3; 2013:115.3 ± 0.2; 2014:114.7 ± 0.2; 2015:116.0 ± 0.2; 2016:117.6 ± 0.2; and 2017:117.1 ± 0.2 mg/dL) and women (2012:119.5 ± 0.3; 2013:120.7 ± 0.2; 2014:119.8 ± 0.02; 2015:120.8 ± 0.2; 2016:122.7 ± 0.1; and 2017:123.8 ± 0.2 mg/dL). The percentage with LDL‐cholesterol ≥160 mg/dL also increased significantly ( P < 10 −9 ) in men and women. Similar results were obtained for ages 40 to 75 years olds (corresponding to ACC/AHA guidelines). Conclusion: These results provide additional evidence that declining blood LDL‐cholesterol levels observed following the ATP‐III recommendations, did not further decline (actually increased) following the 2013 ACC/AHA recommendations.